Evaluation of the biomethane yield from anaerobic co-digestion of nitrogenous substrates - Allen, Eoin (Environmental technology, 2013)
This paper examines three substrates for anaerobic co-digestion: abattoir waste; cheese waste and food waste. These substrates were assessed in detail for suitability for biomethane production. Biomethane potential (BMP) assays were carried out in mono and co-digestion for the three substrates and two mixes: T1 (40% abattoir waste; 50% cheese waste and 10% food waste on a wet weight basis) and T2 (30% abattoir waste; 40% cheese waste and 30% food waste). The C:N ratio of both mixes was below optimum. Low levels suggest that the production of free ammonia (NH3) in semi-continuous digestion was of primary concern. Both mixes were digested in a semi-continuous process for 25 weeks. The recommended operating condition for T1 was a loading rate of 3 kg VS mn(-3) day(-1) at a retention time of 23 days. The biomethane yield was 305 L CH4 kg(-1) volatile solids (VS) which was 87% of the BMP value and equivalent to 61% biodegradability. For T2 (with the higher C:N ratio) a higher loading rate of 4kg VS mn(-3) day(-1) at a lower retention time of 15 days was recommended. The biomethane yield was 439 L CH4 kg(-1) VS (99% of the BMP value and 84% biodegradibility). At these conditions, levels of total ammonical nitrogen (TAN) were 4109 and 4831 mg L(-1) for T1 and T2, respectively. These values are on the large side according to the literature. The temperature was reduced to 35 degrees C to minimize toxicity associated with TAN. Ratios of volatile acids to bicarbonate were typically in the range of 0.2-0.3 suggesting stable operation